2016
DOI: 10.1042/bcj20160580
|View full text |Cite
|
Sign up to set email alerts
|

The Rim101 pathway contributes to ER stress adaptation through sensing the state of plasma membrane

Abstract: Abbreviation list: DMSO, dimethyl sulfoxide; ER, endoplasmic reticulum; ESCRT, endosomal sorting complex required for transport; PM, plasma membrane; PtdSer, phosphatidylserine; Rim21C, C-terminal cytosolic region of Rim21; WT, wild-type 2 Summary statementThe sensor protein for plasma membrane lipid asymmetry, Rim21, detects ER stress by sensing alterations in the state of the plasma membrane, and triggers an adaptation response via the Rim101 pathway. 3 AbstractYeast cells sense alterations in the plasma mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…6g ). Rim101 activation through manipulation of plasma membrane lipids has been reported to depend on the Rim21 sensor complex which includes RIM21 , RIM9 , DFG16 , and RIM8 [ 26 , 27 ]. This raised the question whether DG-induced cell death would also depend on this sensor complex.…”
Section: Resultsmentioning
confidence: 99%
“…6g ). Rim101 activation through manipulation of plasma membrane lipids has been reported to depend on the Rim21 sensor complex which includes RIM21 , RIM9 , DFG16 , and RIM8 [ 26 , 27 ]. This raised the question whether DG-induced cell death would also depend on this sensor complex.…”
Section: Resultsmentioning
confidence: 99%
“…The latter option has recently been introduced by Obara and Kihara. They found that Rim101 signalling can be triggered by ER stress (Obara and Kihara 2017 ). ER stress can affect lipid asymmetry and thus Rim101 could be triggered in order to compensate for these changes.…”
Section: Sensing Lipid Stress At the Pmmentioning
confidence: 99%
“…A recent study investigated whether Rim101 signalling depends on ER-PM contact sites (Obara and Kihara 2017 ). The authors revealed that Rim101 signalling occurred mostly at sites different from ER–PM contact sites.…”
Section: The Role Of Mcs In Lipotoxicitymentioning
confidence: 99%
“…Several observations indicate that alterations in lipid homeostasis induce mechanisms involved in protein quality control. Conditions that perturb lipid biosynthesis, that alter the lipid compositions of the plasma membrane and endomembranes or that affect the lipid droplet content of cells were all reported to trigger ER stress and activation of the unfolded protein response (UPR) 182 183 184 185 186 187 188 . In contrast to acute ER stress, which induces PCD 189 190 , the lipid-associated induction of ER stress appears to be linked to compensatory mechanisms directed to reinstate lipid biosynthesis and lipid metabolism and to promote cell survival 191 192 193 194 195 .…”
Section: Ph Control Stress Tolerance and Longevitymentioning
confidence: 99%